أثر برنامج تدريبي في تنمية الوظائف المعرفية - داوي, صبرينة; تعوينات, علي (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة الى معرفة اثر برنامج تدريبي مقترح في تنمية الوظائف المعرفية (الانتباه والإدراك) لدى الأطفال المصابين باضطراب طيف التوحد متوسط الشدة، بالاعتماد على المنهج شبه التجريبي بطريقة المجموعة الواحدة عدد افراد العينة 10 أطفال يعانون من اضطراب طيف التوحد المتوسط الشدة ، وهم من جنس الذكور يتراوح سنهم مابين 04 و06 سنوات ، يدرسون بالمركز الطبي البيداغوجي لتيجلابين بومرداس ، للسنة الدراسية 2018/2019 ، وقد أسفرت النتائج عن وجود فروق دالة احصائيا في اختبار النضج العقلي كولومبيا بين القياسين القبلي و البعدي لصالح القياس البعدي ،مما يؤكد ويوضح الاثر الايجابي للبرنامج المقترح في تنمية و تعزيز الوظائف المعرفية المدروسة والتي تؤثر في التعلم الاكاديمي، وبالتالي تسهل الدمج التربوي و الاجتماعي لهذه الفئة من الأطفال مستقبلا. Abstract: : This study aimed to know the effect of a proposed training program on developing cognitive functions (attention and perception) in children with moderateseverity autism spectrum disorder, based on the quasi-expérimental approach in the onegroup method for children; the number of sample 10 individuals suffering from the average autism spectrum and they are of the male sexa Their age ranges between 04 and 06 years, studying at the Pedagogical Medical Center Tidjelabine Boumerdes, for the academic year 2018/2019, and the results resulted in statistically significant differences in the Colombia mental maturity test between the pre and post measurements in favor of the post measurement, which confirms and explains the positive impact of the proposed program in Development and strengthening of studied cognitive functions that affect academic Learning, and thus facilitate the educational and social integration of This group of children in the future.
مقال
Keywords: اضطراب طيف التوحد ؛ الانتباه ؛ الإدراك؛ البرنامج التدريبي; autisme Spectrum disorder ; Attention ; perception ; training program